Faktor-Faktor Yang Mempengaruhi Kejadian Malaria Pada Ibu Hamil Di RSUD Kwaingga Kabupaten Keerom - Wahyuni, Sri; Martina Mogan; Heni Voni Rerey (Jurnal Medicare, 2025)
Malaria in pregnant women is a health problem that remains prevalent in endemic areas, including Keerom Regency. Malaria infection during pregnancy can cause various complications for the mother and fetus. This study aimed to determine factors affecting the incidence of malaria in pregnant women at Kwaingga Regional Hospital, Keerom Regency. This study used a case-control design with 94 pregnant women participating: 47 with malaria (cases) and 47 without malaria (controls). The variables studied included gestational age, parity, education level, anemia level, adherence to antenatal care (ANC) visits, and adherence to bed net use. Data analysis was performed using the Chi-Square test with a significance level of α = 0.05. The results showed that all variables studied were significantly associated with malaria incidence in pregnant women, with a p-value <0.05. It was concluded that biological, behavioral, and social factors play a significant role in the incidence of malaria in pregnant women.